A Missing Link? Capabilities, the Ethics of Care and the Relational Context of Energy Justice. Issue 2 (3rd April 2021) - Groves, Christopher; Shirani, Fiona; Pidgeon, Nick; Cherry, Catherine; Thomas, Gareth; Roberts, Erin; Henwood, Karen
ABSTRACT : Difficulties experienced in obtaining energy services have been represented as unjust because of how they can prevent people from realising primary human capabilities. Capabilities are relational, being embedded within complex interdependencies between people and socio-material systems. These complexities can cause problems for approaches to energy justice that are based on concepts of welfare rights. We argue that the ethics of care, with its emphasis on relationality as the ground of obligation, and particularly on how social relationships are bound up with power and responsibility, can provide firmer foundations for thinking about energy injustice. Care ethicists distinguish between different forms of dependency, some necessary, others oppressive. Using qualitative longitudinal methods to explore people's experiences of energy challenges and energy vulnerability can show how power and responsibility within dependency relationships can change over time. With data from a longitudinal study in South Wales, we explore how everyday energy-using practices can become entangled with harmful forms of dependency. We show how the everyday ethical evaluation of these relationship undertaken by participants harmonises with the ethics of care. Our data show the utility of understanding relationships of dependence within the energy system in terms of responsibility and irresponsibility, in order to better understand energy injustice.